THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE - Azzahra Thahir, Bayna; Lestariningsih, Marsudi (JURNAL EKBIS, 2024)
This research aims to find out and analyze the effect of compensation and work discipline on employees' performance, with work motivation as the intervening variable at CV Concept Global Media. The independent variables were compensation and work discipline, while the dependent variable was employees' performance and work motivation as the intervening variable. The population was employees at CV Concept Global Media consisting of 45 people. Furthermore, the data collection technique used saturated sampling. The data analysis technique used Partial Least Square SmartPLS 3.0. The results concluded that compensation and work discipline had a positive and significant effect on employees' performance. Additionally, compensation had a positive and significant effect on work motivation. Work discipline has a positive and significant effect on employees' performance. In addition, work motivation may not mediate the effect of compensation on employees' performance. Likewise, work motivation may not mediate the effect of work discipline on employees' performance.